Influence of Organic Matter Content on Engineering Properties of Clays - Yue Gui; Qiumin Zhang; Xiaqiang Qin; Jianfei Wang (Advances in Civil Engineering)
Most natural sedimentary clay contains organic matter, and even a small amount of organic matter will have a great impact on the physical and mechanical properties of clay. In order to clarify the influence of organic matter content on clay soil, the illite-quartz mixture was mixed with natural amorphous peat soil (organic matter content is 50%) in different proportions for studying the influence of different organic matter contents on the physical properties (specific gravity, Gs; moisture content, w; void ratio, e; liquid limit, wL; plastic limit, wp; plasticity index, Ip) and shear characteristics (cohesion, c; friction angle, φ) of clay soil. The experimental results found that, with the change of organic matter content, the specific gravity and void ratio of clay changed linearly, while the water content, Atterberg limit, shear strength, cohesion, and friction angle changed nonlinearly with the increase of organic matter content. Moisture content and Atterberg limit have a turning point when OC = 7.5%. Shear strength, cohesion, and friction angle all have obvious turning points when OC = 7.5% and OC = 37.5%. The variation of moisture content and Atterberg limit with organic matter content indicates that OC = 7.5% may be the limit value for the different forms of organic matter in the clay. When OC ≤ 7.5%, the organic matter in clay is in the bound state; when OC > 7.5%, the bound organic matter reaches saturation; and the free organic matter gradually increases. The change law of shear strength characteristics with organic matter content shows that the interaction between minerals and organic matter exhibits different shear characteristics under different organic matter content. When OC ≤ 7.5%, clay shows mineral properties, when 7.5% < OC ≤ 37.5%, clay shows mineral-free organic matter properties, and when OC > 37.5%, clay shows free organic matter properties.